N-terminal Myristoylation Enhanced the Antimicrobial Activity of Antimicrobial Peptide PMAP-36PW - Liu, Yongqing; Li, Shengnan; Shen, Tengfei; Chen, Liangliang; Zhou, Jiangfei; Shi, Shuaibing; Wang, Yang; Zhao, Zhanqin; Liao, Chengshui; Wang, Chen (Frontiers in Cellular and Infection Microbiology, 2020)
Drug-resistant bacteria infections and drug residues have been increasing and causing antibiotic resistance and public health threats worldwide. Antimicrobial peptides (AMPs) are novel antimicrobial drugs with the potential to solve these problems. Here, a peptide based on our previously studied peptide PMAP-36PW was designed via N-terminal myristoylation and referred to as Myr-36PW. The fatty acid modification provided the as-prepared peptide with good stability and higher antimicrobial activity compared with PMAP-36PW in vitro. Moreover, Myr-36PW exhibited effective anti-biofilm activity against Gram-negative bacteria and may kill bacteria by improving the permeability of their membranes. In addition, the designed peptide Myr-36PW could inhibit the bacterial growth of Staphylococcus aureus ATCC 25923 and Pseudomonas aeruginosa GIM 1.551 to target organs, decrease the inflammatory damage, show an impressive therapeutic eﬀect on mouse pneumonia and peritonitis experiments, and promote abscess reduction and wound healing in infected mice. These results reveal that Myr-36PW is a promising antimicrobial agent against bacterial infections.